Combination of hemoglobin and left ventricular ejection fraction as a new predictor of contrast induced nephropathy in patients with non-ST elevation myocardial infarction - Ugur, Murat; Uluganyan, MAHMUT; ULUGANYAN, MAHMUT; Ekmekci, Ahmet; Bozbay, Mehmet; Karaca, Gurkan; Cicek, Gokhan; Koroglu, Bayram; Tusun, Eyup; Murat, Ahmet; Turan, Burak; Uyarel, Huseyin; et al. (My University, 2014)
Background: Hemoglobin concentration (Hb) and left ventricular ejection fraction (EF) are known predictors of contrast induced nephropathy (CIN). We hypothesized that combination of Hb concentration and left ventricular EF is superior to either variable alone in predicting contrast induced nephropathy in patients with acute coronary syndrome (ACS). Material and methods: Consecutive patients with ACS were prospectively enrolled. Patients considered for invasive strategy were included. Baseline creatinine levels were detected on admission and 24, 48 and 72 hours after coronary intervention. 25% or 0,5 umol/L increase in creatinine level was considered as CIN. Results: 268 patients with ACS (mean age 58±11 years, 77% male) were enrolled. Contrast induced nephropathy was observed in 26 (9.7%) of patients. Baseline creatinine concentration, left ventricular EF, and Hemoglobin was significantly different between two groups. Contrast volume to estimated glomerular filtration rate ratio (OR: 1.310, 95% CI: 1.077-1.593, p=0.007) and the combination of Hb and left ventricular EF (OR: 0.996, 95% CI: 0.994-0.998, p=0.001) were found to be independent predictors for CIN. Hb × LVEF ≤690 had 85% sensitivity and 57% specificity to predict CIN (area under curve: 0.724, 95% CI: 0.625-0.824, p<0.001). In addition, Hb × LVEF ≤690 had a negative predictive value of 97% in our analysis Conclusions: The combination of Hb and left ventricular EF is better than either variable alone at predicting CIN in patients with ACS that undergone percutaneous coronary intervention. The prediction was independent of baseline renal function and volume of contrast agent.
Keywords: Contrast Induced Nephropathy; Anemia; Ejection Fraction; Non-ST Elevation Myocardial Infarction